Survey Upah Kerja Restoran di Kabupaten Bandung pada Masa Pandemi - Erislan Erislan; Moch. Sambas (Syntax Corporation, 2023)
The COVID-19 pandemic has had an impact on low-income workers, most of whom have experienced significant salary cuts. This happened due to government policy in an effort to suppress the spread of covid 19 by making an Emergency Community Activity Restriction Program (PPKM) policy for the Java Bali area starting on July 4, 2021. The regulation strictly restricts the activities of citizens. Employers who can still survive provide options for workers, namely working with a salary of 20-30% of the initial salary in the work agreement or being laid off because it requires company efficiency, which means experiencing a salary reduction of 80%. Based on the results of a survey conducted by the Indonesia Business Coalition for Women Empowerment (IBCWE) in May and December 2020. Workers who experienced a suspension of work again by 26% and workers who were still working, but experienced a reduction in working hours and wages by 55%. Bandung Regency itself, not a few companies cut their employees' salaries because production has dropped dramatically, some even completely close their companies, as happened in Dayeuhkolot District. There were massive layoffs from two garment companies that went out of business. Employees are temporarily laid off or working hours are reduced, taking turns with other employees which of course has an impact on reducing salaries. The formulation of the problem of how to determine the working hours of MSME workers in Bandung Regency during the pandemic and how to determine salaries based on these working hours. This study aims to determine the payroll applied by business actors in Bandung Regency during the pandemic. The research method used is qualitative descriptive. Meanwhile, the expected output of this research is to contribute data and facts related to the impact of the pandemic to business actors and the government through publication in accredited national journals.